If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + y + -76 = 0 Reorder the terms: -76 + 2x + y = 0 Solving -76 + 2x + y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '76' to each side of the equation. -76 + 2x + 76 + y = 0 + 76 Reorder the terms: -76 + 76 + 2x + y = 0 + 76 Combine like terms: -76 + 76 = 0 0 + 2x + y = 0 + 76 2x + y = 0 + 76 Combine like terms: 0 + 76 = 76 2x + y = 76 Add '-1y' to each side of the equation. 2x + y + -1y = 76 + -1y Combine like terms: y + -1y = 0 2x + 0 = 76 + -1y 2x = 76 + -1y Divide each side by '2'. x = 38 + -0.5y Simplifying x = 38 + -0.5y
| x=.5(2x-10-3) | | 291+x=360 | | v+2.59=4.69 | | 2y-2+4y-32+y+8=360 | | x-61=12.5 | | 12Y+17=161 | | X^2-18x+81=2001 | | 27.48+x=3.29x | | -5x-6+4x=12 | | 3x-6(-5x+17)=162 | | -3y-1+2y=-1 | | (4x-40)/2=(2x-90)x4 | | (4x-40)/2=(2x-90)4 | | -1/8(8y-72) | | (4x-40)/2=(2x-90)*4 | | v-2.14=4.4 | | w*8+4=13 | | Y=x^2+9x-112 | | 1/3y-1/3=-6 | | 5x-12+5=-3 | | 1x-2x/5=3 | | 4x+75=9x+95 | | 4(3x-1)-5(3x-2)=2(x+2)-5x | | 2(2x)-3(x+5)=-13 | | 12-4*0+1=0 | | -10.2=-3.4c | | 5(x/5-3)=30 | | 5x+27-2x=0 | | kx^2-2x+3=0 | | -3/8b=0 | | 3x+7-3x= | | 7/4*9/14 |